Venous thromboembolism prophylaxis practices in hematology/oncology patients admitted to neurological intensive care units - Alsuhebany, Nada; Alfehaid, Lama; Alodhaibi, Danah; Mahdali, Madhawi; Almohareb, Sumaya; Alshaya, Abdulrahman (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveVenous thromboembolism (VTE) presents a significant challenge for neurocritically ill patients with cancer due to the combined risks of thrombosis and bleeding. This study aimed to describe VTE prophylaxis practices among this high-risk population.MethodsThis is a retrospective cohort study at a tertiary teaching hospital. Data were obtained for all patients admitted with neurocritical illness with a history of either solid tumors or hematological malignancies. The main outcome was the incidence of bleeding events in the neurocritical care unit (NCCU) using the International Society on Thrombosis and Haemostasis (ISTH) criteria. Other secondary outcomes were the incidence of thrombotic events, NCCU length of stay, and in-hospital mortality.ResultsOut of the 168 patients screened, 43 patients were included, of which 38 patients (88.3%) had solid tumors, and 5 patients (11.6%) had hematologic malignancies. The majority of patients (81.3%) received chemical VTE prophylaxis during hospitalization. The incidence of major bleeding events was reported in 8 patients (21%) with solid tumors and one patient (20%) with hematologic malignancies, with no cases of thrombosis during hospitalization. Compared to the literature, the incidence of major bleeding events in our study is lower than indicated by a previous report on high bleeding risks in similar patient populations. The median duration of hospital stay was five days in the NCCU and 17 days in the hospital, with a 30-day mortality rate of 14%.ConclusionOur study highlights the complexity of managing VTE prophylaxis in neurocritically ill cancer patients, emphasizing the need for a careful risk-benefit assessment. The absence of thrombotic events suggests effectiveness; however, bleeding risks warrant caution. These findings underscore the importance of individualized care and highlight the need for further research to refine prophylaxis protocols, thereby ensuring both safety and efficacy in this high-risk group.